The Effect of a Combined Mindfulness and Yoga Intervention on Soldier Mental Health in Basic Combat Training: A Cluster Randomized Controlled Trial - Nassif, Thomas H.; Gutierrez, Ian A.; Smith, Carl D.; Jha, Amishi P.; Adler, Amy B. (Depression and Anxiety, 2023)
Background. Depression, anxiety, and sleep problems are prevalent in high-stress occupations including military service. While effective therapies are available, scalable preventive mental health care interventions are needed. This study examined the impact of a combined mindfulness and yoga intervention on the mental health of soldiers in Basic Combat Training (BCT). Methods. U.S. Army soldiers (N=1,896) were randomized by platoon to an intervention or training-as-usual condition. Soldiers in the intervention condition completed Mindfulness-Based Attention Training (MBAT), engaged in daily 15 min mindfulness practice, and participated in 30 minutes of hatha yoga 6 days per week. Surveys were administered at baseline (T1, prior to training), week 4 of BCT (T2), week 6 (T3), and week 9 (T4). Results. A significant time-by-condition interaction predicting positive screens for depression found that screens decreased at a faster rate from T1 to T4 in the intervention condition (-12.6%) compared to training-as-usual (-7.2%) (b=−0.18, SE=0.07, p=0.028). While positive anxiety screens decreased over time across conditions, the time-by-condition interaction found no significant differences in the rate of these decreases by condition (b=0.09, SE=0.09, p=0.273). A significant time-by-condition interaction predicting positive screens for sleep problems found that sleep problems decreased in the intervention condition (-1.4%) but increased in training-as-usual (2.0%) (b=−0.68, SE=0.16, p=0.027). Conclusion. The mindfulness and yoga intervention was associated with a greater reduction in positive screens for depression and sleep problems among soldiers during high-stress training. Limitations include reliance on self-report and the inability to disaggregate the effects of mindfulness versus yoga. Mindfulness and yoga may enable personnel in high-stress occupations to sustain their mental health even in the context of significant psychological demands. This trial is registered with NCT05550610.